Strategi Keamanan Maritim di Asia Tenggara: Kerjasama Diplomasi maritim di ASEAN - Muh. Fadry Amry Guricci; Seniwati Seniwati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Southeast Asia, as a strategic region connecting two of the world's major oceans, faces a range of maritime security challenges, both traditional, such as territorial disputes in the South China Sea, and non-traditional, such as piracy, human trafficking, and illegal fishing. This article discusses maritime security strategies in the region, with a primary focus on maritime diplomacy cooperation under the ASEAN framework. Using maritime security theory, maritime diplomacy, and a literature analysis, the article examines the effectiveness of ASEAN's regional cooperation in addressing the complexities of maritime threats in Southeast Asia. The study's findings indicate that although challenges such as strong nationalism and geopolitical disputes still hinder collaboration, ASEAN has made progress in building more structured cooperation mechanisms. The article emphasizes that strengthening maritime diplomacy between countries, as well as with global actors, is an effective step to ensure stability, security, and sustainability in Southeast Asia's maritime domain.